Identification of Affective Learning, Affective Aspect, and Measuring Tools Used in Nursing Education: a Systematic Review - Haryani, Ani; Gayatri, Dewi; Novieastari, Enie; Nuraini, Tuti; Sulistyowati, Dita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Attitude is one of the domains in the competence of nurses. Attitudes are formed through internalizing learning experiences related to how students feel when they learn. Affective Learning refers to learning that enriches emotions, belief systems, and professional values. In nursing education, the attitude aspect is often the goal of learning but is not followed by learning strategies and evaluations to achieve these learning goals. The research aims to identify effective learning strategies and measure tools used to identify changes from the affective skills or affective aspect studied. A systematic review using electronic literature databases published from year 2012 until 2022. Scopus Search, Clinical Key Nursing, ProQuest, Ebscohost, SAGE Journals, and Science Direct. The research design criteria are randomized control trials and quasi-experimental studies. Eligibility assessment by conducting a critical appraisal using tools from the Joanna Briggs Institute critical appraisal. 15 articles met the criteria, consisting of five Randomized Control Trial research articles, and 10 Quasi-experimental articles. The results of a systematic review show that Simulations using standardized patients and reflective practice are learning methods that are often used. Empathy is the most researched affective aspect followed by communication, self-efficacy, and self-confidence. Empathy as the most affective aspect studied was measured using The Jefferson Empathy Scale. Learning interventions aimed to improve an affective aspect of nursing students are not single, but integrate various learning methods. This is also influenced by the affective aspect developed in learning, which is not a single aspect, and uses several measuring tools to assess its development.